2003
DOI: 10.1557/proc-798-y2.3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Bulk GaN Crystals at High Pressure and High Temperature

Abstract: We report the growth and characterization of bulk GaN single crystals by temperature-gradient recrystallization at high pressure and high temperature (HPHT), using apparatus adapted from that used to synthesize gem-grade diamond crystals. The bulk crystals are grown on seeds that were synthesized by hydride vapor phase epitaxy (HVPE) and subsequently removed from their sapphire substrate. Our largest crystals to date are 15×18 mm in diameter; however, the process is scalable to 50 mm and above. The crystals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…3). We have determined the polarity of the crystals by singlecrystal X-ray diffraction, as described elsewhere [21], and found that the large hexagonal face is (0 0 0 1) Ga. Similar polarities of prismatic GaN crystals grown in a Na/Ga alloy have been reported [22].…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…3). We have determined the polarity of the crystals by singlecrystal X-ray diffraction, as described elsewhere [21], and found that the large hexagonal face is (0 0 0 1) Ga. Similar polarities of prismatic GaN crystals grown in a Na/Ga alloy have been reported [22].…”
Section: Resultssupporting
confidence: 53%
“…The total level of impurities in our crystals has been reduced from approximately 10 20 cm À3 [21] to the 10 18 cm À3 range by improving the purity of our raw materials. The principal impurities are O, H, and C, with lower levels of transition metals.…”
Section: Resultsmentioning
confidence: 99%
“…Below this temperature HAI is more stable [15]. When using NH 4 F as a mineralizer for GaN growth, a fluoride amine complex (intermediate) was obtained at 400 1C; on the other hand, D'Evelyn et al [16] were able to grow GaN crystals at 700 1C. Thus, temperatures over 500 1C favor the formation of the hexagonal phase of both GaN and AlN from either ammonobasic or ammonoacidic solutions.…”
Section: Using Gallium-containing Intermediate As Nutrientmentioning
confidence: 99%
“…However, while it is easy to synthesize powders, the group III nitrides AlN, GaN and InN, are notoriously difficult to prepare in single crystal form. Several workers have demonstrated that microcrystalline gallium and aluminum nitride can both be prepared in supercritical ammonia [4][5][6][7] obtaining high-quality bulk crystals as large as only a few millimeters is challenging. Here, we briefly report our efforts on the growth of GaN bulk crystals by the ammonothermal technique.…”
Section: Introductionmentioning
confidence: 99%